In silico studies on pyrazine derivatives for identifying potential inhibitors of PIM-1 kinase - Amena Ali, Abuzer Ali, Mohd. Washid Khan, Abutahir, Ibraheem Husain, Kuldeep Patel, Vivek Asati (Journal of Applied Pharmaceutical Science, 2020)
PIM-1 kinase (PIM-1K) modulates multiple cellular functions and is evolving as a drug target for cancer. In search of potential PIM-1 inhibitors, we report herein the 3D-QSAR as well as docking studies on 3-(pyrazin-2-yl)-1H-indazole derivatives. Based on the 3D-QSAR study, the generated pharmacophore was utilized for the virtual screening of thousands of compounds (compds) from ZINC database against PIM-1K. Four top-ranked compds, ZINC05885218, ZINC05888770, ZINC08652441, and ZINC73096248, were selected by virtual screening study. The study results of molecular docking suggested that certain key residues were significant for interactions of ligand–receptor due to the formation of hydrogen bonds with Glu171, Glu121, Lys67, Asp128, Asp131 and Asp186 of PIM-1K. Virtually screened compds displayed resemblance in binding interactions within the PIM-1Ks catalytic pocket in comparison with their corresponding crystal structures. The ADRRR.2 emerged as the potential pharmacophore hypothesis and was employed for the generation of model of 3D-QSAR which gave good statistical values of q2 and r2 using partial least square analyses (r2 = 0.922, q2 = 0.8629) for the best model. The study results revealed that ZINC73096248 could serve as a prototype compd for developing novel PIM-1K inhibitors.
Keywords: Anticancer, PIM-1 kinase, docking, 3D-QSAR, ZINC database.